2015
DOI: 10.5761/atcs.oa.14-00075
|View full text |Cite
|
Sign up to set email alerts
|

A UK Single Centre Retrospective Analysis of the Relationship between Haemodynamic Changes and Outcome in Patients Undergoing Prolonged Left Ventricular Assist Device Support

Abstract: IntroductionAlthough heart transplantation remains the gold standard for the treatment of end-stage heart failure with an average 2-year survival rate of 80%, 1) its epidemiological impact is limited by organ availability. 2) Over the last 5 years, rotary left ventricular assist devices (LVADs) have been used increasingly either as a bridge to transplant or for permanent support. In spite of their clinical efficacy, LVADs remain associated with serious complications which compromise outcome. However, the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The simulation outcome for patient 1 does show a leftward shift of the pressure–volume loops for the left and right ventricles with adequate ventricular volumes, although the gain in ejection fraction may be initially limited. On the contrary, it is true that further improvement is observed over a period of time [ 84 ] making LVAD insertion a suitable option for this patient. Because of the potential complications related to the associated co-morbidities, the unanimous clinical decision to decline any further intervention but continue with medical treatment and eventually palliation may have been the way forward although further argument in favour of LVAD insertion would be the recent evidence supporting the “obesity paradox” in cardiac surgery [ 85 ], which is currently the subject of a hot debate.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation outcome for patient 1 does show a leftward shift of the pressure–volume loops for the left and right ventricles with adequate ventricular volumes, although the gain in ejection fraction may be initially limited. On the contrary, it is true that further improvement is observed over a period of time [ 84 ] making LVAD insertion a suitable option for this patient. Because of the potential complications related to the associated co-morbidities, the unanimous clinical decision to decline any further intervention but continue with medical treatment and eventually palliation may have been the way forward although further argument in favour of LVAD insertion would be the recent evidence supporting the “obesity paradox” in cardiac surgery [ 85 ], which is currently the subject of a hot debate.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Cerebrovascular disorders and percutaneous site (cannula site and driveline) infections are the most frequent complications after VAD implantation. It has been reported that VAD-related infections occur in 9.8%-51.9% of patients at an average of 68 days to 9.2 months after implantation and can have a major influence on survival.…”
Section: Introductionmentioning
confidence: 99%